Home-prepared soymilk: Potential to alleviate protein-energy malnutrition in low-income rural communities in South Africa? - Sara S. Duvenage; Wilna H. Oldewage-Theron; Abdulkadir A. Egal; Gabriel N. Medoua (AOSIS, 2013)
Research findings reported pronounced protein and some energy shortfalls for school-aged children and female caregivers in rural communities in Qwa-Qwa, South Africa. The household gardening project was expanded to include soy cultivation. Subsequently, a process was developed for home-preparation of soymilk to support macronutrient consumption. The limited explorative experimental approach included chemical analysis for total protein (Kjeldahl digestion, spectrophotometric determination), total carbohydrate (Anthone method) and total lipid content (extraction, Gravimetric method, separation). Total energy content was calculated. All results were benchmarked against equivalents. Duplicate analysis of samples, respectively prepared from 1:2 (n = 6) and 1:4 (n = 4) volume ratios of rehydrated minced soybeans : water for cooking of soy mash, indicated statistically-significant differences for reported nutrients (p ≤ 0.05). Comparison between sourced commercial soymilk products for drinking indicated no statistical differences (p > 0.05). Although statistically-significant shortfalls were indicated for nearly all such values for home-prepared soymilk (1:4 ratio) against industrial 'SoyCow' soymilk and values reported in the South African database for standardised nutrient composition of food (p ≤ 0.05), a much-needed contribution will be made to protein (and energy) intake through consumption of the product. More efficient extraction (possibly double mincing of rehydrated soybeans and more efficient pressing of cooked soy mash) should be explored, followed by an intervention study to evaluate the impact of daily consumption of home-prepared soymilk on the nutritional status of children in low-income communities. The development of recipes to promote the inclusion of undissolved fibre from the soymilk extraction process (okara) in dishes prepared at household level, such as bread, is recommended. Navorsing het beduidende proteïen en minder ernstige energie te korte uitgewys by skoolkinders en vroulike versorgers in plattelandse gemeenskappe in Kwa-Kwa. Die huishoudelike tuinbouprojek is uitgebrei om soja-verbouing in te sluit en 'n proses is ontwikkel vir die tuisbereiding van sojamelk om makronutriënt inname te bevorder. Die beperkte eksperimentele benadering het chemiese analise vir totale proteïen (Kjeldahlvertering, spektro-fotometriese bepaling), totale koolhidraat (Anthonemetode) en totale lipied inhoud (ekstraksie, Gravimetriese metode, skeiding) ingesluit. Totale energie is bereken en alle resultate is met ekwivalente vergelyk. Duplikaatanalise van sojamelkmonsters, onderskeidelik berei van 1:2 (n = 6) en 1:4 (n = 4) volume verhoudings van gehidreerde gemaalde sojabone : water vir die kook van die sojapulp, het statisties-beduidende verskille uitgewys (p ≤ 0.05). Geen statisties-beduidende verskille is gevind in die makronutriëntwaardes van kommersiële sojamelkprodukte wat gedrink kan word nie (p > 0.05). Alhoewel statisties-beduidende tekorte vir bykans alle soortgelyke waardes van tuisbereide sojamelk (1:4) teenoor die industrieel bereide 'SoyCow' produk en waardes gerapporteer in die Suid Afrikaanse databasis vir gestandardiseerde nutriëntsamestelling van voedsel (p ≤ 0.05) waargeneem is, sal inname van die tuisbereide produk tog 'n belangrike bydrae tot proteïen (en energie) inname kan lewer. Die effektiwiteit van 'n verbeterde nutriëntekstraksie, byvoorbeeld deur 'n dubbel-maalproses en meer effektiewe pers van die gekookte sojapulp, moet ondersoek word. 'n Intervensiestudie om die effek van daaglikse sojamelk inname op die voedingstatus van kinders in lae-inkomste bemeenskappe te meet, word aanbeveel. Verder word aanbeveel dat resepte ontwikkel word om die onopgeloste vesel wat oorbly na die melkmaak proses (okara) in huishoudelike geregte in te sluit, byvoorbeeld in die bereiding van brood.